Stephen Rupp, Allegories of kingship: Calderón and the anti-Machiavellian tradition. The Pennsylvania State University Press, University Park, Pennsylvania, 1996; 187 pp. - Margaret Rich Greer (Nueva Revista de Filología Hispánica, 1998)
Se reseñó el libro: Allegories of kingship: Calderón and the anti-Machiavellian tradition.